Targeting rare tumors: new focus for clinical research in China. Issue 1 (28th November 2022) - Wang, Shuhang; Jiang, Yale; Miao, Huilei; Fang, Yuan; Jiang, Ning; Yu, Yue; Ma, Peiwen; Tang, Qiyu; Cui, Dandan; Fang, Hong; Huang, Huiyao; Fan, Qi; et al.
Abstract : Rare tumor has a huge unmet medical need without standard regimens, calling for novel therapeutic interventions. The National Cancer Center of China identified a threshold of incidence for rare tumor as 2.5/100, 000, based on the characteristics of Chinese population. Molecular profiles for rare tumor patients in China further provided prospects for precise and individualized targeted treatment. An ongoing phase II clinical trial, the PLATFORM study, is the first trial tailored for rare solid tumors in China, featured by molecule‐guided therapeutics. With the promulgation of supportive policies to encourage the development of innovative drugs for rare tumors in China, opportunities will be provided for these patients and the gap will be filled in the treatment of rare tumors. Abstract : In this timely Commentary, Prof. N. Li and colleagues discuss the challenges related to rare tumors definition, clinical trials, and therapies, with a focus on China.